Evaluation of self-efficacy in Spanish nurse prescribers: are they qualified to safely and effectively prescribe medication and health devices? - Gomis-Jimeno, Francisco Javier; Vaismoradi, Mojtaba; Lillo-Crespo, Manuel (Frontiers in Medicine, 2025)
IntroductionIn Spain the Royal Decree 1302/2018 of October 22nd regulates nurse prescribing of medication and health products (NPMHP) with at least 1 year of professional experience as a nurse. It provides nurse prescribers (NPs) with the authority to prescribe medications and health products, throughout established protocols published in the Official Spanish State Bulletin (BOE). In line with this, assessing the self-efficacy of NPs is relevant in its beginnings and by using tools such as the standardized nurse prescribing self-efficacy scale (NP-SES) it is possible to accurately evaluate their knowledge on NPMHP. This research aimed at exploring the Spanish accredited NPs’ perceptions on NPMHP knowledge and the impact of these prescribers’ confidence on their professional practice.MethodsA cross-sectional study was performed with Spanish NPs invited to complete the online version of the NP-SES. The cross-sectional study collected qualitative and quantitative data from a convenience sample of 14 NPs accredited in the last years at a health organization in Spain, encompassing various profiles, in terms of clinical specializations, complementary training and years of experience, for NPMHP.ResultsAll respondents expressed a positive perception of the implementation of NPMHP in the healthcare system and recognized NPMHP usefulness in enhancing patient safety, increasing patient satisfaction and therapeutic adherence, by strengthening interprofessional collaboration, and improving the efficiency of healthcare delivery. Specific areas where additional support and training may enhance nurses’ confidence and competence in prescribing roles have been identified.ConclusionThere is a need for education in the national undergraduate and postgraduate training of nurses regarding NPMHP as well as an adequate guidance on prescribing responsibilities in practice. In addition, the NPMHP protocols should be developed regarding nurses’ roles in prescribing medication within the multidisciplinary healthcare team. Future research should include prescribing audits to validate self-efficacy scores in the context where NPMHP takes place.